INTERACTIVE TECHNOLOGIES IN TEACHING A FOREIGN LANGUAGE - Oybekovna, Daminova Gulbahor; Usmanovna, Nazarova Gulchehra; Rashidovna, 3Mamadjanova Mohimir (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the application of new interactive technologies in teaching English. The purpose of this study is to analyze the effectiveness of using interactive technologies in the process of teaching a foreign language at a university. Interactive learning technologies include clearly planned learning outcomes, interactive methods, tools and forms that stimulate the learning process, cognitive and mental conditions and procedures to achieve the planned results. The main result of our study is an analysis of the impact of using interactive methods on the acquisition of communicative competence and personal development. The main findings assess the importance of using interactive technologies in the educational process. The use of new information technologies in teaching English improves the quality of education.